Síntese e caracterizacão estrutural de semicondutores magnéticos diluídos do tipo (Zn,Mn)O - Souza, Antônio Oliveira de (2011)
The (Zn1-x, Mnx)O system was synthesized in the 0.03 ≤ x ≤ 0.20 composition range by lyophilization and heat treatment, using ZnO powder (as matrix) and manganese acetate (for the doping) as precursors. The heat treatments were conducted in free atmosphere, at different temperatures and periods of time. The as-prepared samples were structurally and magnetically characterized by thermogravimetry, differential scanning calorimetry and magnetometry. This analysis showed that the solubility limit for the manganese on the ZnO matrix is 5 at.%. The lattice parameter and the crystallite mean size increased monotonically with the manganese concentration and, beyond the solubility limit, there is precipitation of a spinel-like phase of the ZnMn2O4 type. Magnetization as a function of applied magnetic field revealed that, at room temperature, the (Zn, Mn)O solid solutions are paramagnetic. The magnetic susceptibility was shown to be inversely proportional to the temperature of the thermal annealing of lyophilized material. All these results are discussed according to the hypothesis current in the literature on the ferromagnetic order for the (Zn, Mn)O compound.